Environmental education and conservation attitudes in the students of the Institution secondary school “Sacred Heart of Jesus” of Phara – Puno -Peru. - Chipana Nina, Ynocencio (2024)
The study aimed to evaluate the connection between environmental education and attitudes towards preservation in the students of the “Sagrado Corazon de Jesús” secondary education establishment in Phara-Puno-Peru. It is basic research, with a bivariate relationship and quantitative approach, with an observational and transversal design with the participation of 50 students in the survey called Education and environmental preservation. The results show direct, significant relationships with different levels of weak to moderate between preservation attitudes with education in climate change, health, eco-efficiency and risk and disaster management, which in general allow us to conclude that there is a moderate positive relationship between environmental education and preservation attitudes (Rho is r=0.432 and p=0.002